Women in middle age and old age: living conditions and mental health by race/color in the Brazilian context - de Queiroz Soares, Bianca; Rabelo, Doris Firmino; Seixas da Cruz, Simone (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
The aim was to compare living conditions and mental health (Common Mental Disorders - CMD) among white, mixed race and black women in middle age and old age in Brazil. A descriptive, cross-sectional study with a quantitative approach was carried out in a virtual environment. A convenience sample of 545 middle-aged and older women in Brazil completed an online form with a sociodemographic information sheet and the Self-Reporting Questionnaire (SRQ-20). Bivariate analyses (chi-square of independence and Student's t-test) and a factorial ANOVA (p≤0.05) were performed and effect sizes were calculated. The results indicated differences by race/color in terms of family configuration and socioeconomic conditions, with a higher proportion of black women in the worst indices. With regard to mental health, white women were more protected and mixed race and single black women had more CMD. The data indicated the complexity involved in mental health and that the ageing of black, mixed race and white women takes place in different social and economic contexts. A more dignified and healthy old age for all women requires public policies that address racial disparities on multiple levels, considering the specificities of brazilian racism.